Effect of different cropping systems and nutrient sources on growth, productivity and economics of direct seeded basmati rice (Oryza sativa) - VERMA, RAKESH KUMAR; SHIVAY, YASHBIR SINGH; GHASAL, PRAKASH CHAND (The Indian Journal of Agricultural Sciences, 2017)
A field experiment was conducted during rainy (kharif) seasons of 2014 and 2015 at New Delhi to evaluate the effects of cropping systems and nutrient sources on growth, root parameters, yield attributes, yields and economics of direct seeded basmati rice (Oryza sativa). On pooled average basis, the highest growth parameters, yield attributes, viz. effective tillers, spike length, grains/panicle and grain weight (g)/spike and yields were associated with inclusion of summer mungbean in the rice-based cropping systems. On pooled average basis, among the nutrient management strategies, 50% recommended dose of fertilizers (RDF) + 25% recommended dose of nitrogen (RDN) through vermicompost (VC) + biofertilizer was found to be best for most of the yield attributes, grain (3.72 t/ha) and straw (7.14 t/ha) yields and gross returns (105.14 × 103 Rupees/ha) followed by 50% RDF + 25% RDN through leaf compost (LC) + biofertilizer. Similarly, the highest root growth length (4.93 cm/cm3), root volume (16.41 cm3) and root dry matter (4.87 g) were registered under treatment 50% RDF + 25% RDN through VC + biofertilizer followed by 50% RDF + 25% RDN through leaf compost (LC) + biofertilizer and then 100% RDF. A strong positive correlation (r2=0.89–0.97) was also observed between yield attributes (effective tillers/m2, grains/panicle, grain weight/panicle and panicle weight) and yield of direct seeded basmati rice. Application of 100% RDF proved better and accrued the highest net returns and B: C ratio (1.54). DSBR–wheat–mungbean or DSBR–cabbage–mungbean cropping system in conjunction with 50% RDF + 25% RDN through VC + biofertilizer or 50% RDF + 25% RDN through leaf compost (LC) + biofertilizer significantly improved growth, yield attributes, leading to enhanced productivity and profitability of rice.